Diversidad de Helechos en el Sendero La Esperanza del Parque Nacional La Tigra, Honduras - Hernandez Cibrian, R. K.=700 1 Nelson Sutherland, C.H.; Mejia Ordoñez, T.M.; Borjas Machado, G.A.
(Es, En)
Ilus., 13 ref.
Keywords: TAXONOMIA; BIODIVERSIDAD; HELECHOS; COMPOSICION BOTANICA; HONDURAS